2005
DOI: 10.1385/mn:31:1-3:255
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioning: A Novel Intrinsic Cytoprotective Strategy

Abstract: A concept of tissue-cell adaptation to hypoxia (hypoxic preconditioning) is raised and its corresponding animal model is introduced. A significantly strengthened tolerance to hypoxia and a protective effect of the brain extracts from the preconditioned animals are presented. Changes in animals' behavior, neuromorphology, neurophysiology, neurochemistry and molecular neurobiology during preconditioning are described. Energy saving, hypometabolism, and cerebral protection in particular are thought to be involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…With each additional run of hypoxia we noted that the animal’s tolerance increased. Tolerance time in runs 2, 3, 4, and 5 was approximately 2, 4, 6, and 8 times greater, respectively, than times observed in the first run (Lu et al, 1999, 2005). This demonstrates HPC’s protective role.…”
Section: Hypoxic Preconditioning (Hpc): History and Neuroprotectivmentioning
confidence: 69%
See 1 more Smart Citation
“…With each additional run of hypoxia we noted that the animal’s tolerance increased. Tolerance time in runs 2, 3, 4, and 5 was approximately 2, 4, 6, and 8 times greater, respectively, than times observed in the first run (Lu et al, 1999, 2005). This demonstrates HPC’s protective role.…”
Section: Hypoxic Preconditioning (Hpc): History and Neuroprotectivmentioning
confidence: 69%
“…This occurs primarily at the cellular level and is discussed in detail below. Of clinical significance, the mechanisms underlying plasticity and modulation can point to novel strategies for the prevention and treatment of hypoxic and ischemic injury (Lu et al, 1999, 2005; Wang et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In WbHPC animals, the internal state seems to fluctuate to conform to the available oxygen challenge in the environment in terms of energy conservation (manuscript in preparation), brain plasticity, and antihypoxia factor/gene activation [39][40][41][42][43] (Fig. 1).…”
Section: Mechanisms and Implications Of Hpcmentioning
confidence: 99%
“…Hence, cobalt can be used to mimic hypoxia to increase HIF-α [17,19]. We have proposed that HIF-1α can play a center role in the tolerance time in autoprogressive hypoxic mice [20]. However, Vangeison et al reported that loss of HIF-1α function in neurons reduced neuronal viability during hypoxia.…”
Section: Introductionmentioning
confidence: 99%